Higher Risk of Dyslipidemia With Coformulated Elvitegravir, Cobicistat, Emtricitabine, and Tenofovir Alafenamide than Efavirenz, Lamivudine, and Tenofovir Disoproxil Fumarate Among Antiretroviral-Naive People Living With HIV in China. (1st October 2022) - Sun, Liqin; He, Yun; Xu, Liumei; Zhao, Fang; Zhou, Yang; Zhang, Lukun; Peng, Qiaoli; Zhang, Haitao; Zhang, Qiuyue; Cao, Tingzhi; Song, Ying; Wang, Siyuan; et al.
Abstract : Background: We aimed to examine the evolution of blood lipids and compare the risk of dyslipidemia between antiretroviral-naive people living with HIV who received tenofovir disoproxil fumarate (TDF), lamivudine (3TC), and efavirenz (EFV) (TDF + 3TC + EFV) and those who received coformulated elvitegravir, cobicistat, emtricitabine, and tenofovir alafenamide (E/C/F/TAF). Methods: We retrospectively reviewed the medical records of 2343 antiretroviral-naive people living with HIV who initiated TDF + 3TC + EFV or E/C/F/TAF. A propensity score matching method was used to compare longitudinal changes of blood lipids between the 2 groups. Results: By using 1:3 matching ratio, we included 253 and 91 matched patients in TDF + 3TC + EFV group and E/C/F/TAF group, respectively. The levels of total cholesterol, triglyceride, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol were higher in E/C/F/TAF group than those in TDF + 3TC + EFV group at 3, 6, 9, and 12 months (Wilcoxon test, all P s < 0.05), except for high-density lipoprotein cholesterol at 9 and 12 months. The cumulative rates of hypercholesterolemia, hypertriglyceridemia, and high LDL-C in PLWH with normal lipid levels in E/C/F/TAF group were higher than those in TDF + 3TC + EFV group (hypercholesterolemia, 59.7% vs 21.5%, P < 0.001; hypertriglyceridemia, 69.5% vs 46.3%, P < 00.001; and high LDL-C, 41.5% vs 14.2%, P < 0.001). Multivariate analysis showed treatment with E/C/F/TAF was associated with a significantly higher risk of hypercholesterolemia [adjusted hazard ratio (HR), 4.12; 95% confidence interval (CI): 2.65 to 6.41], hypertriglyceridemia (adjusted HR, 1.69; 95% CI: 1.18 to 2.43), and high LDL-C (adjusted HR, 4.60; 95% CI: 2.66 to 7.97). Conclusions: We concluded that treatment with E/C/F/TAF resulted in higher risks of dyslipidemia compared with TDF + 3TC + EFV.